(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Customer Relationship Management (CRM) encompasses activities andprocesses intended to help an organization understand, communicate with, andservice the needs of, customers and prospects. The main driver for CRM is theunderlying philosophy that successful customer engagement, and thereforesuccessful business, is based on the ability to build ‘meaningfulrelationships’ with customers